Current Diagnosis and Management of Immune Related Adverse Events (irAEs) Induced by Immune Checkpoint Inhibitor Therapy - Kumar, Vivek; Chaudhary, Neha; Garg, Mohit; Floudas, Charalampos S.; Soni, Parita; Chandra, Abhinav B. (Frontiers in Pharmacology, 2017)
The indications of immune checkpoint inhibitors (ICIs) is set to rise further with the approval of newer agents like tremelimumab and atezolimumab for use in patients with advanced stage mesothelioma and urothelial carcinoma respectively. More frequent use of ICIs has improved our understanding of their unique side effects, which are known as immune-related adverse events (irAEs). The spectrum of irAEs has expanded beyond more common manifestations such as dermatological, gastrointestinal and endocrine effects to rarer presentations involving nervous, hematopoietic and urinary systems. There are new safety data accumulating on ICIs in patients with previously diagnosed autoimmune conditions. It is challenging for clinicians to continuously update their working knowledge to diagnose and manage these events successfully. If diagnosed timely, the majority of events are completely reversible, and temporary immunosuppression with glucocorticoids, infliximab or other agents is warranted only in the most severe grade illnesses. The same principles of management will possibly apply as newer anti- cytotoxic T lymphocytes-associated antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1/PD-L1) antibodies are introduced. The current focus of research is for prophylaxis and for biomarkers to predict the onset of these toxicities. In this review we summarize the irAEs of ICIs and emphasize their growing spectrum and their management algorithms, to update oncology practitioners.